Improving the method of low‐temperature anisotropy of magnetic susceptibility (LT‐AMS) measurements in air. (24th July 2016) - Issachar, R.; Levi, T.; Lyakhovsky, V.; Marco, S.; Weinberger, R.
Abstract: This study examines the limitations of the method of low‐temperature anisotropy of magnetic susceptibility (LT‐AMS) measurements in air and presents technical improvements that significantly reduce the instrumental drift and measurement errors. We analyzed the temperature profile of porous chalk core after cooling in liquid nitrogen and found that the average temperature of the sample during the LT‐AMS measurement in air is higher than 77K and close to 92K. This analysis indicates that the susceptibility of the paramagnetic minerals are amplified by a factor ∼3.2 relative to that of room temperature AMS (RT‐AMS). In addition, it was found that liquid nitrogen was absorbed in the samples during immersing and contributed diamagnetic component of ∼−9 × 10 −6 SI to the total mean susceptibility. We showed that silicone sheet placed around and at the bottom of the measuring coil is an effective thermal protection, preventing instrument drift by the cold sample. In this way, the measuring errors of LT‐AMS reduced to the level of RT‐AMS, allowing accurate comparison with standard AMS measurements. We examined the applicability of the LT‐AMS measurements on chalk samples that consist <5% (weight) of paramagnetic minerals and showed that it helps to efficiently enhance the paramagnetic fabric. The present study offers a practical approach, which can be applied to various types of rocks to better delineate the paramagnetic phase using conventional equipment. Key Points: We offer practical approach using conventional equipment to better define paramagnetic fabric by LT‐AMS measurements By using silicon sheet protection we manage to achieve high measuring accuracy and to obtain reliable LT‐AMS fabric Temperature analysis suggests that LT‐AMS measurements in air amplifies paramagnetic susceptibility by a factor of ∼3.2 in chalks